2001
DOI: 10.1074/jbc.m007878200
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Localization of Yeast Nfs1p Is Required for Cell Survival

Abstract: Saccharomyces cerevisiae Nfs1p is mainly found in the mitochondrial matrix and has been shown to participate in iron-sulfur cluster assembly. We show here that Nfs1p contains a potential nuclear localization signal, RRRPR, in its mature part. When this sequence was mutated to RRGSR, the mutant protein could not restore cell growth under chromosomal NFS1-depleted conditions. However, this mutation did not affect the function of Nfs1p in biogenesis of mitochondrial iron-sulfur proteins. The growth defect of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
94
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(103 citation statements)
references
References 45 publications
(53 reference statements)
8
94
1
Order By: Relevance
“…Such dual localization of a protein possessing both nuclear and mitochondria-targeting sequences was recently reported for several proteins, including the human RNA helicase MDDX28 (41) and the yeast protein Nfs1p (42). Another interesting example is the yeast repair enzyme Apn1p that apparently possesses a mitochondrial as well as a nuclear localization sequence; in this case, targeting of the enzyme to mitochondria is enhanced by another protein that interferes with nuclear transport of Apn1p (43).…”
Section: Discussionmentioning
confidence: 73%
“…Such dual localization of a protein possessing both nuclear and mitochondria-targeting sequences was recently reported for several proteins, including the human RNA helicase MDDX28 (41) and the yeast protein Nfs1p (42). Another interesting example is the yeast repair enzyme Apn1p that apparently possesses a mitochondrial as well as a nuclear localization sequence; in this case, targeting of the enzyme to mitochondria is enhanced by another protein that interferes with nuclear transport of Apn1p (43).…”
Section: Discussionmentioning
confidence: 73%
“…This divergence in iron metabolism between yeast and human may result in different requirements for Fe-S cluster assembly in yeast versus the higher eukaryotes. Although endogenous yeast Nfs1p (an IscS homolog) cannot be detected in the nucleus by Western blotting, recent nuclear transportation trap analysis and mutagenesis studies (54) clearly indicate that nuclear localization of Nfs1p is essential for cell viability, further underscoring the physiological function of extramitochondrial isc genes. Our studies of the mammalian isc genes have revealed that three mechanisms: alternative start codon utilization in iscS (26), alternative selection of cassette exons in iscU (27), and alternative use of 5Ј donor splice sites in nfu (this article), function in mammalian cells to target isc gene products to different subcellular locations, suggesting a potentially powerful and versatile regulatory mechanism for coordinated control of these proteins in different compartments.…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, a small pool of the single NFS1 gene product is localized in the nucleus [8], but does not play a role in Fe-S protein assembly [9]. In human cell lines, a mitochondrial and a cytosolic/nuclear isoform of the NFS1 homologue (called ISCS) have been observed [10,11], but only the mitochondrial form contributes functionally to the assembly of cellular Fe-S proteins [11].…”
Section: Introductionmentioning
confidence: 99%